Innovative approaches for controlling the material flow in sheet-bulk metal forming processes - Merklein, Marion; Lechner, Michael; Gröbel, Daniel; Löffler, Maria; Schneider, Thomas; Schulte, Robert Karl; Hildenbrand, Philipp (Manufacturing Review, 2016)
Using sheet-bulk metal forming processes the application of bulk forming operations on sheet metals enables the manufacturing of functional components with local wall thickness variations. As these processes come along with a two- and three-dimensional material flow, the control of the material flow is crucial for ensuring a proper filling of functional elements and thus ensuring the components quality. Controlling the material flow can be achieved by different solutions: the local adaption of tribological conditions and the application of process adapted semi-finished parts. In this paper, both solutions as well as their general qualification in two sheet-bulk metal forming processes are presented.
LFT Import::2019-07-29 (2144)
Keywords: Forming; Material flow; Processes